Kualitas Pelayanan Drive Thru Pajak Kendaraan Bermotor Di Samsat Pembantu Pettarani Upt (Unit Pelaksana Teknis) Pendapatan Wilayah Makassar - Utami, Muthiah Fadhilah; Ansari, Muh Isa; Tahir, Muhammad (Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out how good the service quality of vehicle tax drive thru in Samsat Pettarani Assistant UPT (Technical Implementation Unit) Makassar regional revenue. The method used quantitative research methods with descriptive research type with data collection techniques through questionnaires. The sample in this study were 50 people and the sampling method used accidental sampling technique. The results of this study showed that the service quality of vehicle tax drive thru in Samsat Assistant Pettarani UPT (Technical Implementation Unit) Makassar regional revenue showed that the physical appearance aspects of service officers, facilities and infrastructure were very good, then the reliability of service officers in the service completion process it was on time, the responsiveness of service officers responds, provided fast and precise services, as well as guarantees provided by service officers such as timeliness of service completion, transparency, supervision and appropriate legitimacy and empathy aspects of service officers in the form of service officer courtesy, friendliness, not discriminating which showed very well.Keywords: Quality, drive thru service, motor vehicle tax